Digital Storytelling as a Counter-Narrative: A Bibliometric Analysis of the Indonesian Diaspora's Role in Mitigating Islamophobia 2014-2024 - Akbar Aziz Efendi; Lety febriana; Agustinus Heriyanto; Rasman Rasman; Fransiskus Novrianto Pakpahan (Tinta Emas Institute, 2024)
Islamophobia remains a pervasive global challenge, necessitating innovative counter-strategies. This study provides a comprehensive bibliometric analysis of 1,028 Scopus-indexed publications (2014-2024) examining digital storytelling by the Indonesian Diaspora as a counter-narrative against Islamophobia. Through performance analysis and science mapping using VOSviewer, the research reveals distinct intellectual foundations through co-citation analysis, identifying four key clusters: psychological behavior antecedents, social media marketing, SME digital empowerment, and technology acceptance models. Concurrently, bibliographic coupling analysis uncovers three emerging research fronts focusing on digital technology adoption in education, interdisciplinary sustainability pathways, and e-learning success models. While these frameworks provide valuable theoretical foundations, significant limitations persist, particularly the dominance of technocratic approaches that overlook socio-political complexities in Islamophobic discourse. The study concludes by proposing six critical research agendas: platform-specific algorithm optimization, psychological message framing, cultural brokerage roles, sustainable business models, computational social science applications, and digital diplomacy synergies. These findings not only map the current scholarly landscape but also advocate for more integrated, critical approaches to understanding diaspora-led digital counter-narratives in combating global Islamophobia.